PEMBIASAAN KEGIATAN KEAGAMAAN PADA ANAK USIA DINI MENDORONG PERKEMBANGAN NILAI-NILAI AGAMA - Yuyun Lestari (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This study was intended to determine the inculcation of religious values in early childhood through the habituation of religious activities in KB SRIWIJAYA. This research is included in qualitative research, so the problem is discussed through field studies conducted at KB SRIWIJAYA. Data obtained from several sources by means of observation, unstructured interviews, and documentation. From all the data that has been obtained then processed with descriptive analysis. This research has found that the inculcation of religious values in early childhood in KB SRIWIJAYA is carried out every day and the learning is more devoted on Friday. In every activity KB SRIWIJAYA tries to include religious values in each of the activities carried out, for example accustoming students to recite prayers before and after doing activities. The results of the inculcation of religious values can be seen from the attitude of students and students who have begun to change for the better, the awareness of parents who initially paid less attention to the development of children's religion now become more motivated to always pay attention to the development of children's religion, as well as the KB SRIWIJAYA institution have the trust of students' parents and the community that KB SRIWIJAYA is able to produce a generation of qualified Muslims and Muslims.